In Pursuit of Ecosystem-Based Management for Narragansett Bay: An Overview of Previous Models and Roadmap for Future Research. Issue 3 (4th May 2022) - Humphries, Austin; Gorospe, Kelvin; Innes-Gold, Anne; McNamee, Jason; McManus, Conor; Oviatt, Candace; Collie, Jeremy
Abstract: Ecosystem models have emerged as vital tools for evaluating management strategies and are increasingly used by policymakers. We reviewed the history of modeling and identified research gaps based on policy needs for ecosystem-based management of Narragansett Bay (RI, USA)—a highly-impacted system with a history of research and monitoring dating back to the 1950s. There is a need to disentangle the impacts of nutrient reductions versus climate change on species interactions as well as understand the ecological and socio-economic tradeoffs of management actions. Within this context, we consider the following to be important for future research and creation of ecosystem models for Narragansett Bay: (i) account for multi-scale processes and patterns through two-way model coupling; (ii) incorporate human behavior as part of model predictions; and (iii) lessen the impact of model uncertainty by identifying robust management strategies that will sustain resources under a range of potential future scenarios. Ecosystem modeling that builds on prior models and is informed by knowledge gaps will be a powerful tool to operationalize ecosystem-based management in Narragansett Bay and globally, providing sustainable pathways for nature and people.